2019
DOI: 10.1002/cbdv.201900347
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin Exerts Anti‐Obesity Effect in Brown Adipose Tissue

Abstract: Catechins in green tea are well‐known to be effective in reducing the risk of obesity. The purpose of this study was to elucidate the effects of catechins present in green tea on adipocyte differentiation and mature adipocyte metabolism. Treatment of 3T3‐L1 mouse adipocyte during differentiation adipocytes with (−)‐epigallocatechin (EGC) and gallic acid (GA) resulted in dose‐dependent inhibition of adipogenesis. Specifically, EGC increased adiponectin and uncoupling protein 1 (UCP1) transcription in mature adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 26 publications
(48 reference statements)
1
6
0
Order By: Relevance
“…1A). These molecules included epigallocatechin, 14 ursolic acid, 15 carvacrol 16 and other natural products that have been previously shown to have anti-obesity effects, which confirms the feasibility of the screening method. In addition, we identified a compound, epigoitrin (EP), an alkaloid from Radix isatidis , whose structural formula is shown in Fig.…”
Section: Resultssupporting
confidence: 63%
“…1A). These molecules included epigallocatechin, 14 ursolic acid, 15 carvacrol 16 and other natural products that have been previously shown to have anti-obesity effects, which confirms the feasibility of the screening method. In addition, we identified a compound, epigoitrin (EP), an alkaloid from Radix isatidis , whose structural formula is shown in Fig.…”
Section: Resultssupporting
confidence: 63%
“…We found that 0.4 µg/mL of chia seed showed high MMP, directly representing active mitochondrial thermogenesis. In this context, epigallocatechin [28,29] and aloe-emodin [30] have been reported for their anti-obesity potential via the inhibition of adipogenesis and the enhancement of fatty acid oxidation. Figure 4 shows the results for the accumulated oil red O stain concentration in control and chia seed-treated maturing adipocytes after 14 days.…”
Section: Resultsmentioning
confidence: 99%
“…When such cell types have been used to examine the ability of green tea compounds to induce the expression of UCP1 and other genes related to thermogenic potential, positive effects of these compounds have been reported (11,17), i.e., results opposite to those presented herein primary cultures of both brown and white adipocytes. We are not aware of studies with green tea compounds in other established white adipocyte-like cell lines such as C3H10T1/2 or hMADS cells, and thus, we cannot say whether similar outcomes would be observed in all white adipocyte-like cell lines.…”
Section: Established Adipogenic Cell Lines May Not Reflect the Phenotype And Epigenetics Of Primary Cellsmentioning
confidence: 96%
“…These observations are not without precedence in studies in adipocyte-like cell cultures. Several studies have reported an inhibitory effect of GTEs or polyphenols from green tea on adipogenesis in vitro (17,35). Kim et al (17) found that different catechins and gallic acid inhibited the accumulation of intracellular lipids in the 3T3-L1 cell line.…”
Section: Green Tea Compounds Are Negative For Adipogenesismentioning
confidence: 99%
See 1 more Smart Citation